“Your Body Feels Better When You Drink Water”: Parent and School-Age Children’s Sugar-Sweetened Beverage Cognitions - Eck, Kaitlyn M. (Nutrients, 2018)
Sugar-sweetened beverages (SSBs) are a leading source of added sugar in the American diet. Further, ingestion of added sugars from SSBs exceeds recommendations. Thus, interventions that effectively reduce SSB consumption are needed. Focus group discussions with parents (n = 37) and school-aged children between the ages of 6 and 11 years (n = 41) from Florida, New Jersey, and West Virginia were led by trained moderators using Social Cognitive Theory as a guide. Trends and themes that emerged from the content analysis of the focus group data indicated that both parents and children felt that limiting SSBs was important to health and weight control. However, parents and children reported consuming an average of 1.85 ± 2.38 SD and 2.13 ± 2.52 SD SSB servings/week, respectively. Parents and children were aware that parent behaviors influenced kids, but parents reported modeling healthy SSB behaviors was difficult. Busy schedules, including more frequent parties and events as children get older, were another barrier to limiting SSBs. Parents were most successful at limiting SSBs when they were not in the house. This qualitative research provides novel insights into parents’ and children’s cognitions (e.g., beliefs, attitudes), barriers, and facilitators related to SSB ingestion. Consideration of these insights during nutrition intervention development has the potential to improve intervention effectiveness in reducing SSB intake.